Studying the effect of addition a composite of silanized Nano-Al2O3 and plasma treated polypropylene fibers on some physical and mechanical properties of heat cured PMMA denture base material - Omar R Muklif; Intisar J Ismail (College of Dentistry/ University of Baghdad, 2015)
Background: Polymethyl methacrylate (PMMA) is the most commonly used material in denture fabrication. The material is far from ideal in fulfilling the mechanical requirements, like low impact and transverse strength, poor thermal conductivity. The purpose of this study was to evaluate the effect of addition a composite of surface treated Nano Aluminum oxide (Al2O3) filler and plasma treated polypropylene fiber (PP) on some properties of denture base material. Materials and methods: One hundred fifty prepared specimens were divided into 5 groups according to the tests, each group consisted of 30 specimens and these were subdivided into 3 groups (unreinforced heat cured acrylic resin as control group),reinforced acrylic resin with( 0.5%wt Nano Al2O3 and2.5%wt plasma treated PP fibers) group and reinforced acrylic with(1%wt Nano Al2O3 and 2.5%wt plasma treated PP fibers group).The tests were impact strength, transverse strength, indentation hardness(shore D), surface roughness thermal conductivity. The results were statistically analyzed using ANOVA test. Results: A highly significant increase in impact strength, surface hardness, thermal conductivity with the addition of 0.5%wt. (Al2O3) and 2.5%wt PP fiber to(PMMA),also there is a significant increase in surface roughness and non significant increase in transverse strength. At the concentration of 1%wt nano (Al2O3) and 2.5%wt PP fiber there is a highly significant increase in impact strength surface hardness and thermal conductivity. Non-significant differences were shown in transverse strength and significant increase in surface roughness. Conclusion: The addition of a composite of Al2O3 nanoparticles and PP fiber to PMMA improves the impact strength, surface hardness and thermal properties, surface roughness while non-significant difference in transverse strength.